Effects of pulmonary exposure to chemically-distinct welding fumes on neuroendocrine markers of toxicity. Issue 5 (4th March 2017) - Krajnak, K.; Sriram, K.; Johnson, C.; Roberts, J. R.; Mercer, R.; Miller, G. R.; Wirth, O.; Antonini, J. M.
ABSTRACT: Exposure to welding fumes may result in disorders of the pulmonary, cardiovascular, and reproductive systems. Welders are also at a greater risk of developing symptoms similar to those seen in individuals with idiopathic Parkinson's disease. In welders, there are studies that suggest that alterations in circulating prolactin concentrations may be indicative of injury to the dopamine (DA) neurons in the substantia nigra. The goal of these studies was to use an established model of welding particulate exposure to mimic the effects of welding fume inhalation on reproductive functions. Since previous investigators suggested that changes in circulating prolactin may be an early marker of DA neuron injury, movement disorders, and reproductive dysfunction, prolactin, hypothalamic tyrosine hydroxylase (TH) levels (a marker of DA synthesis), and other measures of hypothalamic-pituitary-gonadal (HPG) function were measured after repetitive instillation of welding fume particulates generated by flux core arc-hard surfacing (FCA-HS), manual metal arc-hard surfacing (MMA-HS) or gas metal arc-mild steel (GMA-MS) welding, or manganese chloride (MnCl2 ). Exposure to welding fume particulate resulted in the accumulation of various metals in the pituitary and testes of rats, along with changes in hypothalamic TH and serum prolactin levels. Exposure to particulates with high concentrations of soluble manganese (Mn) appeared to exert the greatest influence on TH activity levels and serum prolactin concentrations. Thus, circulating prolactin levels may serve as a biomarker for welding fume/Mn-induced neurotoxicity. Other reproductive measures were collected, and these data were consistent with epidemiological findings that prolactin and testosterone may serve as biomarkers of welding particulate induced DA neuron and reproductive dysfunction.